Consumption and Class
XIII, 263 p.
Keywords: An edited collection exploring divisions and changes within and between the spheres of consumption and production. Topics include: the relationship between consumption and production; the social construction of consumers; housing and social class mobility; health provision; the role of the 'service class'; and access to higher education. Peter Saunders' work provides the initial stimulus for many of the papers, but all go beyond his narrow conception of a sociology of consumption and his liberal analysis of patterns of social inequality.